Métodos geoelétricos empregados na caracterização e monitoramento de anomalias inerentes à infiltração controlada de vinhaça - Bortolin, José Ricardo Melges [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The vinasse is a liquid waste that results of the ethanol production process, in approximate ratio of 13 liters of vinasse for each ethanol liter. This waste is used as fertilizer in sugar cane plantations because it's mainly rich in potassium, sodium, magnesium, and calcium, but, the excess of vinasse can cause soil and groundwater's contamination. In this thesis, three different volumes of vinasse (60, 300, and 900 liters) were infiltrated into two ditches (A and B) escavated in two geologically distinct areas, and the resultant contamination plume was investigated by mean of four geophysical methods: spontaneous potential (SP), electrical resistivity (ER), induced polarization (IP) and electromagnetic (EM). The first area is located on the Corumbataí Formation, that’s mainly characterized by silty and clayey sediments. The second area is located over sand sediments of the Pirambóia Formation. At the Area 1, anomalies were observed only after the infiltration of 900 liters of vinasse in the ditch B. In the ER method, an electrical resistivity profile showed a low resistivity anomaly in the location where the vinasse was infiltrated. In the IP method, a chargeability profile showed a low chargeability anomaly in the same location. The results of EM and SP methods do not revealed any anomaly that could be correlated with vinasse infiltration. At the Area 2, anomalies were observed after the infiltration of 60 liters of vinasse in the ditch A (EM method) and 300 and 900 liters of vinasse in the ditch B (ER and EM methods). In the ER method, the anomalies were characterized by low resistivity values, contrasting with the high resistivity background values. In the EM method, the anomalies were identified by mean of high values of electrical conductivity. In this case, the results of IP and SP methods do not revealed any anomaly, and could not be correlated with vinasse infiltration. The results obtained at the Area 1 were associated to...

A vinhaça é um resíduo líquido resultante do processo de produção de etanol, na proporção aproximada de 13 litros de vinhaça para cada litro de etanol. Este resíduo é utilizado como fertilizante em lavouras de cana-de-açúcar, pois é rico, principalmente, em potássio, sódio, magnésio e cálcio. Entretanto, o excesso de vinhaça pode causar contaminação do solo e da água subterrânea. Nesta tese, três diferentes volumes de vinhaça (60, 300 e 900 litros) foram infiltrados em duas valas (A e B) escavadas em duas áreas geologicamente distintas, e a pluma de contaminação resultante foi investigada por meio de quatro métodos geofísicos: potencial espontâneo (SP), resistividade elétrica (ER), polarização induzida (IP) e eletromagnético (EM). A Área 1 situa-se na Formação Corumbataí, caracterizada principalmente por sedimentos siltosos e argilosos. A Área 2 está localizada sobre sedimentos arenosos da Formação Pirambóia. Na Área 1, foi possível observar anomalias somente após a infiltração de 900 litros de vinhaça na vala B. No método ER, verificou-se uma anomalia de baixa resistividade próxima à vala. No método IP, a anomalia é caracterizada por reduzidos valores de cargabilidade. Os resultados dos métodos EM e SP não revelaram quaisquer anomalias que pudessem ser correlacionadas ao contaminante. Na Área 2, as anomalias foram observadas após a infiltração de 60 litros de vinhaça na vala A (método EM) e de 300 e 900 litros na vala B (método ER e EM). No método ER, as anomalias foram caracterizadas por reduzidos valores de resistividade, contrastando com os elevados valores de background. No método EM, as anomalias foram identificadas por meio de elevados valores de condutividade elétrica. Neste caso, os resultados de métodos de IP e SP não revelaram quaisquer anomalias correlacionadas ao contaminante. Os resultados obtidos na área 1 foram associados à capacidade de troca catiônica (CTC)...
Keywords: Geophysics; Geofisica; Vinhaça; Resistencia eletrica; Indução eletromagnetica; Residuos organicos como fertilizantes; Condutividade eletrica; Solos - Poluição